2021
DOI: 10.1002/bem.22316
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mobile Phone Use on Tinnitus: A Systematic Review and Meta‐Analysis

Abstract: Tinnitus is a perception of sound in the absence of an external source. The aim of our study was to investigate with a meta-analytical approach, whether mobile phone (MP) use increases the risk of tinnitus. Eight studies reporting the risk of tinnitus in relation to MP use were identified, and six high-quality studies (two cohort studies, one case-control study, and three cross-sectional ones) were included in the metaanalysis. The quality assessment was performed using the Newcastle-Ottawa scale. The risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Various reviews concluded that the excellence of conceptional and experimental execution inversely correlates with the likelihood to report an effect; the more the quality criteria requirements were satisfied in a study, the smaller was the number of detected response in cells or animals (Elwood & Wood, 2019;Simko et al, 2016). A recent review on mobile phone use and tinnitus concluded that study quality is critical (Kacprzyk et al, 2021) and a review focusing on exposure from mobile phone base stations concluded that the more sophisticated the exposure assessment is, the less likely an effect would be reported (R€ o€ osli et al, 2010). For this reason, in our review we only included studies that met a basic set of quality criteria and thus had a lower risk of bias or experimental artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Various reviews concluded that the excellence of conceptional and experimental execution inversely correlates with the likelihood to report an effect; the more the quality criteria requirements were satisfied in a study, the smaller was the number of detected response in cells or animals (Elwood & Wood, 2019;Simko et al, 2016). A recent review on mobile phone use and tinnitus concluded that study quality is critical (Kacprzyk et al, 2021) and a review focusing on exposure from mobile phone base stations concluded that the more sophisticated the exposure assessment is, the less likely an effect would be reported (R€ o€ osli et al, 2010). For this reason, in our review we only included studies that met a basic set of quality criteria and thus had a lower risk of bias or experimental artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have not been studies reporting the search of magnetic materials as constituents of the human inner ear. In this regard, it is to be mentioned that some epidemiological studies found an association between MP use and tinnitus (the perception of a sound in the absence of an external source), while a meta-analysis found no association 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, such use relates to different effects contributing to reducing threats to the establishment of sustainability [94]. The applications related to the different effects of exposure to EMF are numerous; see, e.g., [13,14,17,19,34,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113].…”
Section: Sr and Ma Applicationsmentioning
confidence: 99%